Changes in Water Balance Components Within the Left Bank of the Middle Dnipro in 1961–2020 - Сарнавський, С. П. (Київський національний університет імені Тараса Шевченка, 2023)
The article examines the changes in water balance components within the left bank of the Middle Dnipro during two hydroclimatic periods, 1961-1990 and 1991-2020. The research also covered six key river basins on the left bank of the Middle Dnipro, including Psel, Sula, Vorskla, Trubizh, Supii, and Zolotonoshka. The examination of the modifications in the components of the water balance during the period of the climatic norm from 1961-1990 and the modern climatic period from 1991-2020 revealed a decrease in the average long-term values of precipitation in general by -7.3 mm, river runoff by -5.2 mm, and total evaporation by -2.1 mm. The amount of rain on the left bank of the Middle Dnipro was different in each river basin. In the Psel and Sula basins, there was a significant increase in precipitation, with a difference of 18.4 mm and +0.9 mm, respectively. In the Vorskla, Zolotonoshka, Trubizh and Supii basins, there was less rain by -2.2 to -51.7 mm. The opposite scenario was observed in the variation of total evaporation in the respective river basins. Thus, in the three largest river basins of the Psel, Sula and Vorskla, it increased from 5.6 to 26.7 mm, in all other basins the total evaporation decreased from -0.3 to -47.6 mm. But despite various changes in precipitation and total evaporation, there is a reduction in the volume of river runoff from -1.6 to -8.6 mm. The negative dynamics of river runoff indicators are attributed to negative cumulative values of precipitation and total evaporation. The main cause of these changes is the increase in the average annual air temperature across all studied basins by +1.2 °C, leading to an increase in climate aridity indicators within the left bank of the Middle Dnipro by +0.9 %. Similarly, there was a drop in the runoff coefficient by 0.9 %. In essence, changes in water balance components in the studied area result in more water volume from atmospheric precipitation going towards total evaporation, leading to a loss of the water volume that forms river runoff. This serves as a clear example of the influence of the global increase in air temperature on the reduction of water volume in rivers within the left bank of the Middle Dnipro.

У статті досліджено зміни водно-балансових складових в межах лівобережжя Середнього Дніпра за два кліматичні періоди: 1961-1990 та 1991-2020 рр. Аналіз даних проводився в межах 6 ключових річкових басейнів лівобережжя Середнього Дніпра – Псла, Сули, Ворскли, Трубежу, Супою та Золотоношки. Аналіз зміни складових водного балансу за період кліматичної норми 1961-1990 рр. та сучасний кліматичний період – 1991-2020 рр. продемонстрував в цілому для даної території зменшення середніх багаторічних значень кількості опадів на -7,3 мм, річкового стоку на -5,2 мм та сумарного випаровування на -2,1 мм. Проте в межах окремих басейнів річок лівобережжя Середнього Дніпра результати мають значні відмінності: в басейнах Псла та Сули спостерігалось зростання кількості опадів на +18,4 та +0,9 мм відповідно, а в басейнах Ворскли, Золотоношки, Трубежу та Супою воно було від’ємним – від -2,2 до -51,7 мм. Протилежна ситуація спостерігалась в зростанні (зменшенні) величини сумарного випаровування у відповідних річкових басейнах. Так, в трьох найбільших річкових басейнах Псла, Сули та Ворскли воно зросло від 5,6 до 26,7 мм; у всіх інших басейнах сумарне випаровування зменшилось від -0,3 до -47,6 мм. Але попри різні зміни показників кількості опадів та сумарного випаровування спостерігається скорочення величини річкового стоку від -1,6 до -8,6 мм. Причинами негативної динаміки показників річкового стоку є від’ємні сумарні значення кількості опадів та сумарного випаровування. І головна причина цих змін це зростання середньорічної температури повітря в межах всіх досліджуваних басейнів на +1,2 °С, яка призвела до зростання показників посушливості клімату в межах лівобережжя Середнього Дніпра на +0,9 %, а також аналогічно відбулось падіння коефіцієнту стоку на 0,9%. Відбулись зміни складових водного балансу у досліджуваному районі – більший об’єм атмосферних опадів тепер йде на сумарне випаровування, а тому відбувається втрата об’єму води, що формує річковий стік. Це яскравий приклад впливу глобального зростання температури повітря на зменшення водності річок в межах лівобережжя Середнього Дніпра.
Зміни водно-балансових складових у межах Лівобережжя Середнього Дніпра за 1961–2020 рр.
Keywords: річковий басейн; складові водного балансу; багаторічні зміни; коефіцієнт стоку; коефіцієнт посушливості; лівобережжя Середнього Дніпра.; river basin; water balance components; long-term changes; runoff coefficient; aridity coefficient; left bank of the Middle Dnipro